Good clinical history scores over extensive workup in unmasking a case of galactorrhoea. (7th April 2018) - Pathania, Monika; Malik, Paras; Amisha,; Sharma, Saurabh
Abstract : The clinical presentation of a young woman with galactorrhoea is described in detail including the history and clinical examination findings. While the patient and her family members feared a serious medical condition which had so far been an obscurity despite a number of investigations, we tried to diagnose the patient starting from the basics, which after a proper history revealed a levosulpiride-induced galactorrhoea. This again lays emphasis on the old adage in medical field that 'a proper history and examination are the key to diagnosis'. There are few reports pertaining to levosulpiride-induced galactorrhoea making it a rare side effect of this drug. We further try to discuss the different causes of galactorrhoea in a young non-pregnant woman which can be encountered in clinical practice.